Pengetahuan Masyarakat Tentang Kewajiban Membayar Zakat Maal di Desa Rabi Jonggor Kecamatan Gunung Tuleh - Yarham, M (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2023)
Zakat is one of the pillars of Islam which is always mentioned parallel to prayer. This shows how important zakat is in Islam. Therefore zakat is one of the Islamic Shari'a that must be implemented, so zakat is highly emphasized to people who believe as an effort to increase their faith and piety to Allah SWT. There are many polemics that occur in the issue of zakat, one of which is the payment of zakat maal, so this study aims to determine the extent of public knowledge about the obligation to pay zakat maal. This type of research is descriptive qualitative research, using a phenomenological approach. Data collection methods through observation, interviews and documentation. The results of this study explain that there are still many people or muzakki in Rabi Jonggor Village who do not understand the payment of zakat maal which results in the collection and receipt of zakat maal not being optimal. In the end, the goal of zakat maal which was mandated by Islamic teachings was not achieved so that the number of needy and poor increased from year to year